Gestão de riscos em uma planta industrial de beneficiamento de ouro: estudo qualitativo com APR e HAZOP - Silva, Gabrielly Layla da (Universidade Federal de São Carlos, 2023)
The gold beneficiation process comprises a series of stages, ranging from ore extraction to its processing stage. The activities involved carry a set of significant risks. These risks encompass everything from landslides, explosions, fires to environmental contamination, and impacts on the health of the workers involved. Furthermore, in recent years, numerous disasters in the mining industry have shown harmful consequences when risks are not adequately managed. In this context, risk management along with industrial safety plays an essential role in identifying, evaluating, and controlling potential deviations associated with the process, aiming to protect both workers and the environment. This involves the implementation of preventive measures to minimize accidents and prevent damages, thereby promoting the mining industry's social responsibility. In this regard, the study's purpose is to explore the fundamental concepts of risk management based on the APR (Preliminary Risk Analysis) and HAZOP (Hazard and Operability Study) methodologies. Through the APR methodology, 14 stages were evaluated, and 23 operational deviations were qualitatively identified, with 2 of them assessed as "critical" risks. In the HAZOP methodology, 29 nodes were assessed, and 45 operational deviations were identified, with 14 of them rated as "serious" risks. Furthermore, through the comparison between the two approaches, complementarity between APR and HAZOP was observed, emphasizing that the combination of techniques provides a more comprehensive understanding of the risks involved in gold beneficiation activities, allowing for the identification of critical points and the proposal of corrective actions.
Risk management in an industrial gold processing plant: a qualitative study using APR and HAZOP
Keywords: Beneficiamento do ouro; Segurança industrial; Gestão de riscos; Análise preliminar de riscos; Estudo de perigos e operabilidade; Gold beneficiation; Industrial safety; Risk management; Preliminary risk analysis; Hazard and operability study; ENGENHARIAS::ENGENHARIA QUIMICA